Collaborative Relations Between Islamic Religious Education (PAI)Teachers and Parents in Islamic Education - Adi Wijaya; Ridho Ramadhon (Journal of Research in Islamic Education, 2022)
Parents are the first educational factor in children, but what often happens to parents who are busy at work, assume that their children have received a good education, if their children have been enrolled in a quality or qualified institution. So that the obligations of parents in the world of children's education are all borne by the Islamic religious education teachers in the school. Yet when the child comes home from school, the child still needs education and supervision from the student's parents. As a result, if parents do not pay attention to Islamic religious education in their children. So Islamic religious education for these children is not optimal and can result in a lack of harmony between PAI teachers and students' parents in educating these children. So that what PAI teachers teach at school is not carried out properly at home because of the lack of supervision from students' parents. Therefore, the cooperative relationship between PAI teachers and students' parents in Islamic religious education in children is very important and interesting to discuss in this study. As for this study, the authors used a descriptive qualitative library research methodology in examining how the relationship of cooperation between PAI teachers and parents of students in Islamic religious education in children.